A hipotetização em orações gerundivas sob perspectiva funcional - Melo, Raniere Marques de (2022)
In this thesis, based on North American Functional Linguistics, we treaty about the phenomenon of hypothesizing, in written Brazilian Portuguese, in hypotactic adverbial structures, more precisely, reduced gerund sentences, initiated by the verbs suppose, predict, imagine and considerate. These verbs are classified as dubious epistemic verbs whose lexical nature signals a modal value, mental or cognitive attribute. This research, of a quantitative and qualitative nature, has a descriptive-interpretivist character. Relate to the nature of the sources used to acquire the data, this is a documentary research, since the documents analyzed are texts extracted from two newspapers available on the web - O Estado de São Paulo (SP) and Tribuna do Norte (RN). In this perspective, we analyze the syntactic, semantic and textual-discursive factors that frame the occurrences of adverbial structures distributed in different genres of this sphere of communication. After the investigation, based on the principles of the Functionalist Theory, whose purpose was to verify if these clauses met the identical nuanced of hypotheticity or if there would be a gradation of meanings – continuum – between them, we assume that these non-finite clauses with a hypothetical nuance, although they belong to a larger domain – that of causality –, are autonomous in relation to conditionality. For the analysis of this phenomenon, we based on criteria related to the co-referentiality between the subjects of the clauses, the position of the adverbial, the temporal-mode correlation between the clauses and the lexical-semantic content of the verbs. The analysis allows us to conclude, therefore, that these hypotactic gerundive clauses, beyond to exhibiting a diversity of semantic nuances from the most factual to the least factual, can be distributed on a scale in which the clauses initiated by supposing represent the prototype of the hypothesis, of less factual and of greater eventuality, a factor verified both in its lexical content and in its syntactic, semantic and pragmatic configurations. In turn, those initiated by predict and imagine can co-occur with nuances that follow the flow from lesser to greater factuality. Finally, those represented by the verb consider tend to be more factual, more real, that is, they occur in contexts in which greater causality is required.